Elevated miR-29a expression is not correlated with disease activity index in PBMCs of patients with ankylosing spondylitis. Issue 2 (March 2014) - Huang, Jinxian; Song, Guoxiang; Yin, Zhihua; Luo, Xiuxia; Ye, Zhizhong
Abstract Objectives. Ankylosing spondylitis (AS) is a chronic inflammatory disease characterized by new bone formation. Recent evidence suggests that new bone formation in AS may be due to upregulation of Wnt signaling in the osteoblastic pathway secondary to low serum Dickkopf homolog 1 (Dkk-1) levels. And miR-29a orchestrates osteoblast differentiation through direct targeting and negative regulation of Dkk-1. Methods. We initially validated the expression levels of miR-29a in the peripheral blood mononuclear cells (PBMCs) of AS patients (n = 30), rheumatoid arthritis (RA) patients (n = 30) and healthy controls (n = 30) using real-time quantitative reverse transcription PCR (qRT-PCR). Correlation analysis was assessed between miR-29a level in PBMCs of AS patients and disease activity indexes, including erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), Bath ankylosing spondylitis disease activity index (BASDAI), Bath ankylosing spondylitis function index (BASFI) and modified Stoke ankylosing spondylitis spinal score (mSASSS). Results. Significantly higher expression of miR-29a was observed in PBMCs of AS patients (Ct 9.18 ± 1.96) compared with that in RA patients (10.97 ± 0.70, p < 0.001) and healthy controls (Ct 11.45 ± 1.23, p < 0.001). There was no significant difference between RA patients and healthy controls in miR-29a expression (p > 0.05). Elevated miR-29a expression is not correlated with disease activity index (p > 0.05). A weak correlation was found between elevated miR-29a expression and mSASSS (r = −0.393, p = 0.032). Conclusions. We report for the first time elevated miR-29a expression in PBMCs of patients with ankylosing spondylitis, and miR-29a might be used as a useful diagnostic marker in new bone formation but cannot reflect disease activity.